Processos linguísticos no cartaz de guerra: semiótica e gramática do design visual - Fernandes, José David Campos (2009)
Images produce and reproduce social relations, communicate facts, disclose events and interact with their readers with a force similar to a text made up of words. How eminently imagery gender, the poster, as well as an understanding also requires in its texture a process of persuasion, built by a producer to win your reader. In it, a chain of verbal and non-verbal elements arranged in a paper surface is permeated by strategies that most often go unnoticed by the average reader. Anchored in this perspective, this study aimed to verify the representations of non -verbais elements in this genre are structured in order to influence the look, the reading and the seizure of the messages printed on it. The corpus collected in specialized electronic ments, consisted of a poster produced by the British government, to recruit soldiers during the First World War, and those with whom it maintains dialogue conveyed after its publication. Methodologically, entwined: i) the studies developed by Charles Sanders Peirce (1974), in particular, the different categories and own laws organization of signs; ii) the functionalist approach to grammar of visual design proposed by Kress and van Leeuwen (2000), for whom there is in imagistic texts, a representational metafunction (describes the participants in an action), an interactional (sociointeracionais describes the relationships built by the image ) and other compositional (who combines its entirety); iii) Bakhtin's perspective of the sign, taken in its ideological aspect. The analysis confirmed the hypothesis that the visual code, as well as verbal language has its own forms of representation, in that builds relationships and interactional is meaningful relationships from their architecture. In this sense, it is said that the war poster is a semiotic whose wealth today needs to be explored, since its engineering responds to an arsenal of multiple possibilities presented by technological advancement of information and communication - due to occupy various spaces in world - but little has attracted the interest of linguistic research. Ultimately, the investigation brought to light how these posters were used by several leaders of different countries, as a tool to "sell" the idea of war for the population. It can be said then that the posters studied establish a text physical contact with the reader-observer, who performs the critical activity of disclosure in relation to reading, in search of seizure of precalculated meanings and horizons by the producer of these printed genres.